THE INFLUENCE OF THE ANGLE OF SHELVE-MOTIVATORS TO INTENSIFY OF THE SALTING PROCESS UNDER DRUM-TUMBLING - Konstantin Vasilievich Kostenko; Andrey Aleksandrovich Bratsikhin; Aleksey Alekseevich Borisenko; Vyacheslav Alekseevich Chernigovskiy (Вестник Северо-Кавказского федерального университета, 2022)
The results of mathematical modeling .of the processes of internal stress and cycles of optimal an-gle of shelve set into drum tumbler definition are presented meat treatment changing.